Boardroom management : a book of readings - Egwuonwu, Ronald (Lagos, Nigeria : Stride Associates Ltd., 1994)
This volume examines corporate governance practice in Nigeria. covering topics that include the Boardroom; guidelines for successful appointment of a successful Board; problems of Nigerian Boards; making Nigerian Board work among other topics.
Includes bibliographical references and index.
osa 06/08/2018
Loans
Keywords: Directors of corporations; Corporate governance; Nigeria